A New Method Based on Laplace Transform and Its Application to Stability of Pipe Conveying Fluid. (24th January 2017) - Wen, H. B.; Yang, Y. R.; Li, P.; Li, Y. D.; Huang, Y.
Abstract : A new differential transformation method is developed in this paper and is applied for free vibration problem of pipes conveying fluid. The natural frequencies, critical flow velocities, and vibration mode functions of such pipes with several typical boundary conditions are obtained and compared with the results predicted by Galerkin method and finite element method (FEM) and with other results archived. The results show that the present method is of high precision and can serve as an analytical method for the vibration of pipes conveying fluid.